Analisis Pengaruh Motivasi Terhadap Kinerja Karyawan (Studi Empiris Pada Pt Sari Husada Tbk Yogyakarta) - Fx Pudjo Wibowo (FEB Universitas Sultan Ageng Tirtayasa, 2017)
To prepare a company in facing free commerce in the future and competition becomes stricter between companies, the company should straighten up its management, its strategy, and its resource including its human resource. By using the resource effectively and efficiently, it may give the company a better result. Employee as part of the resource should do their job as good as possible as expected by company. The research which takes place in PT Sari Husada Tbk, Yogyakarta, has some aims. The first aim is to examine the influence of individual characteristic toward employee’s performance. Thirdly, if has the aim to examine the influence of job situation toward employee’s performance. Finally the research would like to examine how far the individual, job, and job situation characteristic on the whole can influence the employee’s performance. The research employs the random sampling method likert scale is being employed to evaluate the score. Data collecting is obtained by using library study and field study (interview, observation and questionnaire). The obtained data is processed by the help computer with its SPSS program (Statistical Program for Social Science) 10.0 for window. The data is analyzed some tests, such as validity and reliability test with cronbach’s technique, regression assumption test with multicolinearity, heteroskedastisitas, autocorrelation and statistic test that employ product moment and linear regression test, determination coefficient ( R2), and partial determination coefficient (r2). The result of the research could be used for a consideration in next policy determining process generally in terms of human resource management and particularly in motivating farce to increase employee’s performance in Sari Husada company Yogyakarta. The result of the research shows that: Individual characteristic has direct influence significantly toward employee’s performance. Job characteristic a significantly influence toward employee’s performance. Job situation characteristic has a significant influence toward employee’s performance. Individual job and job characteristic on the whole have significant influence toward employee’s performance.